High resolution infrared spectroscopy in astronomy: proceedings of an ESO workshop held at Garching, Germany, 18 - 21 November 2003 - Käufl, Hans Ulrich; Siebenmorgen, Ralf; Moorwood, Alan F. M. (Springer, 2005)
Two rather specialized new instruments for ESO's VLT, VISIR CRIRES, spawned the idea for this workshop. CRIRES is a dedicated very high resolution infrared spectrograph. VISIR comprises a high resolution spectroscopic mode. Both instruments will combine the sensitivity of an 8m-telescope with the by now well established reliable operation of VLT-facility instruments. High resolution here means that lines in cool stellar atmospheres and HII-regions can be resolved. The astrophysical topics discussed in this rather specialized workshop ranged from the inner solar system to active galactic nuclei. There are many possibilities for new discoveries with these instruments, but the unique tool, which becomes available through high-resolution infrared spectroscopy is the observation of molecular rotational-vibrational transitions in many astrophysical environments. Particularly interesting and surprising in this context was, that many papers on modeling and laboratory spectroscopy were presented which seem to indicate, that astronomical observations are lagging a bit behind in this field. The papers presented at this workshop are an interesting mix of reports from existing high resolution facilities, reports on modeling efforts of synthetic spectra and reports on laboratory spectra. In that sense it was again established, that there is a fruitful exchange between molecular physics and astronomy. TOC:Instrumentation and Observational Highlights.- Young Stars, Hot Stars, LBVs, Novae, SNe, ISM-1.- Normal MS Stars, Old Stars, Active Stars, ISM-2.- Solar Systems, Brown Dwarfs.- Our Solar System
Literaturangaben
Keywords: Konferenzschrift -- München, 2003 -- Garching; Konferenzschrift -- 2003 -- Garching, München; Infrarotastronomie